The Correlation of Body Morphological Size Toward the Body Weight of PO Steers and Heifers - Efendy, Jauhari; Prihandini, P W; Sulistya, T A (ANIMAL PRODUCTION, 2015)
Abstract. The study was conducted to determine the correlation between the body morphology size  of  PO steers and heifers which kept in the group housing of Litbangtan Models. The materials of this study used 24 PO steers and heifers (each cow was 15 to 18 months old). The  data were analyzed using descriptive statistics and correlation analysis. Due to the significant value, it stated that the body length and chest circumference influenced positively to the gain of the weight body of PO steers and heifers . The value of determination analysis (R2) both PO steers  and heifers was 92.70% and 86.80%; It indicated that the gain of the body length size and chest circumference would  increase the body weight. The result of calculation shown that the average of body weight of PO steers and heifers after having used two body morphological measurement (body length and chest circumference) was relativeely close to the real measurement. This phenomenon indicated that the body length and chest circumference had a close relationship with the body weight either in PO steers and heifers. Key words: PO steers and heifers, body morphological size, body weight Abstrak.  Penelitian ini dilaksanakan untuk menentukan korelasi antara ukuran morfologi tubuh PO steers dan heifer yang dipelihara di kandang kelompok Litbangtan Model. Materi yang digunakan dalam penelitian ini adalah 24 PO steer dan heifer (masing-masing berumur 15 sampai 18 bulan). Data dianalisis menggunakan deskriptif statistik dan analisis korelasi. Berdasarkan nilai signifikan, dinyatakan bahwa panjang badan dan lingkar dada berpengaruh positif terhadap peningkatan bobot badan PO steer dan heifer. Nilai koefisien determinsasi (R2) PO steer dan heifer adalah 92,70% dan 86,80%; mengindikasikan bahwa peningkatan ukuran panjang badan dan lingkar dada akan meningkatkan bobobt tubuh. Hasil perhitungan menunjukkan bahwa rataan bobot tubuh PO steer dan heifer setelah menggunakan dua ukuran morfologi tubuh (panjang badan dan lingkar dada) serupa dengan ukuran nyata. Fenomena ini menunjukkan bahwa panjang badan dan lingkar dada berkaitan erat dengan bobot tubuh pada PO steer maupun heifer. Kata kunci: PO steer dan heifer, ukuran morfologi tubuh, bobot tubuh